Analisis Hubungan Lama Menderita Diabetes Mellitus Dengan Kualitas Hidup Penderita Diabetes Mellitus - Ifa Roifah (Akademi Keperawatan Dharma Husada Kediri, 2016)
Diabetes mellitus if doesn’t treated properly can cause various complications in organs such as the eyes, kidneys, nerves and blood vessels of the heart that will harm the soul or affect a person's quality of life. The purpose of this research was to know relationship long suffering diabetes mellitus with the quality of life of people with diabetes mellitus. The design of the study was analytic corelasional with cross sectional approach. Research of variable that is long suffering diabetes mellitus as the independent variable and the dependent variable as a quality of life. Population research namely whole sufferers of diabetes Mellitus at internist disease room in the Wahidin Sudiro Husodo Hospital Mojokerto as much as 103 patients. The samples were taken with the techniques of systematic sampling as much as 81 respondents. Data collected by questionnaire WHOQOL instruments, then the result of pengunpulan data processing data is done editing, coding, scoring and tabulating and tested with test speaman rho. Spearman rho test results retrieved data ρ value = 0,027 <α = 0.05 so that H1 is accepted so there is a connection between the long suffering with kualits life of sufferers of diabetes mellitus in internist disease room in the Wahidin Sudiro Husodo Hospital Mojokerto. Low quality of life occur because respondents are already feeling tired and tired with the treatment process has already lived in a long time, so they feel resigned to the situation that is happening will they be healed or not of disease processes that affect them. Especially the Family expected to have family members suffering from diabetes mellitus to always provide good family support in the form of encouragement, communicating medical treatment to keep his health and direct when got health information. Key Words : Diabetes Mellitus, Qualiity Of Life, long suffering